DOCUMENTARY OF COVID-19 EDUCATION JOURNEY - Sarbunan, Thobias (Al'Adzkiya Journal, 2021)
To the present day, Covid19 has become the star of phenomena. Many of the gaps in education, colourful stories, have emerged as a consequence of the pandemic education; research and innovation as the eyes of the educational body; on the one side, modern countries have been successful in pandemic education, but sad stories come from developing countries, and underdevelopment countries have been terrified by pandemic education until I have written this article. Thousands of papers on science and innovation have had a significant effect on scientific results, but this is just a snapshot of a narrative on the distorted trajectory of pandemic education. However, in-depth analyses of whether and how to continue education in the midst of the pandemic also had an impact on the pandemic education. In addition; digital, internet, synchronized, Asynchronize, distance learning, remote learning has been used as an approach that underpins the policies of each country's current global circumstances. Technology, social and humaniora are in the process of research and have shown a measurable path for pandemic education. The primary focus of pandemic education research was meaningful visionary education; what, when, where, or which measurable approach [is and would be] to solve local and global challenges. So, through this article, I conducted narratively to leverage educational society insight in order to achieve a visionary education system. I concluded that visionary education would establish significant education from a local and global viewpoint.